2020
DOI: 10.1177/0300060520966478
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of postoperative antithrombotic therapy after left atrial appendage occlusion

Abstract: Objective This meta-analysis explored the safety and effectiveness of different anticoagulant regimens after left atrial appendage occlusion (LAAO). Methods Databases, such as PubMed, MEDLINE, EMBASE, Web of Science, and Cochrane Library, were searched to identify eligible studies according to the inclusion criteria. The incidences of events, including device-related thrombus (DRT) formation, stroke, systemic thromboembolism, bleeding, cardiovascular mortality, and all-cause mortality, were analyzed using R ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Actually, there are many other factors that affect the efficacy of LAA closure, including antithrombotic therapy. 25 , 26 As there have been no randomized controlled trials of antithrombotic therapy in LAA closure, this must be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there are many other factors that affect the efficacy of LAA closure, including antithrombotic therapy. 25 , 26 As there have been no randomized controlled trials of antithrombotic therapy in LAA closure, this must be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Few metanalyses have been performed incorporating data from registries and randomized studies comparing LAAO to pharmacological stroke prevention. Li et al included 32 studies (n = 12,326) in a meta-analysis comparing an OAC-based strategy to APT following LAAO [77]. Information was primarily derived from observational studies and a large propensity-score matched analysis of early Watchman trials [78].…”
Section: Comparing Strategiesmentioning
confidence: 99%
“…Moreover, the use of VKA has been limited due to its high requirements for patient compliance, narrow therapeutic window, and interaction with multiple foods and drugs (Shendre et al, 2018). Furthermore, previous studies deduced that DOACs play an important role in the treatment of patients who underwent LAAO (Asmarats et al, 2020;Li et al, 2020). Several clinical trials have demonstrated the efficacy and safety of DOACs in preventing post-PCI and stent thrombosis in NVAF patients and AF patients with coronary heart disease, particularly showing a lower incidence of major bleeding events than warfarin (VKA) (Cimmino et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Meta-analyses, which have been published previously, included a total of 32 studies with 4,474 patients, indicating that DOACs have good prospects for development and may serve as alternatives to VKAs in the future. However, the study had several limitations that should not be overlooked; most of the studies included in the meta-analysis were single-arm studies and the level of evidence was not high; in addition, heterogeneity was analyzed, but no source of heterogeneity was identified for all-cause mortality (Li et al, 2020). Therefore, more extensive RCTs are needed to confirm the efficacy and safety of DOACs in post-LAAO patients.…”
Section: Figurementioning
confidence: 99%